2013
DOI: 10.1007/s10964-013-0024-4
|View full text |Cite
|
Sign up to set email alerts
|

Sleep Deprivation, Low Self-Control, and Delinquency: A Test of the Strength Model of Self-Control

Abstract: Recent work provides evidence that sleep deprivation is positively related to delinquency. In this study, we draw on Baumeister and colleagues' strength model of self-control to propose an explanation for this association. Specifically, we argue that low self-control is the construct that bridges the relationship between sleep deprivation and delinquency. To test the proposed model, we examine survey data drawn from a longitudinal multi-city cohort study of adolescents who were followed from birth through age … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
89
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 128 publications
(93 citation statements)
references
References 51 publications
3
89
0
1
Order By: Relevance
“…These two studies underscore the importance of both academic and cognitive factors for understanding possible developmental pathways linking sleep to adolescent behavior problems and risk-taking. Third, Meldrum et al (2015) found the association between sleep problems and delinquency (a latent factor comprised of substance use, non-violent delinquent behaviors, and violent behaviors) to be mediated by low self-control, even after accounting for prior delinquency, neighborhood context, parenting practices, unstructured peer socialization, and depression. Fourth, using Add Health data, McGlinchey and Harvey, (2015) found a late bedtime in adolescence (M age = 16) to predict cigarette use, alcohol abuse, illicit drug use, criminal activity, and emotional distress 6 years later (M age = 21.8), with all but one of these associations (alcohol abuse) still significant when controlling for parent-child attachment and peer delinquency.…”
Section: Overview Of Special Issue Contributionsmentioning
confidence: 96%
“…These two studies underscore the importance of both academic and cognitive factors for understanding possible developmental pathways linking sleep to adolescent behavior problems and risk-taking. Third, Meldrum et al (2015) found the association between sleep problems and delinquency (a latent factor comprised of substance use, non-violent delinquent behaviors, and violent behaviors) to be mediated by low self-control, even after accounting for prior delinquency, neighborhood context, parenting practices, unstructured peer socialization, and depression. Fourth, using Add Health data, McGlinchey and Harvey, (2015) found a late bedtime in adolescence (M age = 16) to predict cigarette use, alcohol abuse, illicit drug use, criminal activity, and emotional distress 6 years later (M age = 21.8), with all but one of these associations (alcohol abuse) still significant when controlling for parent-child attachment and peer delinquency.…”
Section: Overview Of Special Issue Contributionsmentioning
confidence: 96%
“…The second aim of the study was to investigate the role of psychopathic features for the associations between sleep and delinquent behaviour. Based on our previous results (Aronen, E. T., Laajasalo, T., Backman, H., Saukkonen, S., Salmi, V., Jokela, M. and Kivivuori, J., unpublished data) and earlier literature in adults (Hare, 1970;Meldrum et al, 2015), we hypothesized that controlling for psychopathic features would diminish the size of the effect between sleep and delinquent behaviour. Finally, we also controlled for parental supervision in all of the analyses, as it is a variable known to be linked positively to the amount of sleep among adolescents (Adam et al, 2007) and negatively to youth delinquency (Clinkinbeard et al, 2011).…”
Section: Introductionmentioning
confidence: 94%
“…Interest was sparked by studies showing that sleep loss is related to diminished behavioural response inhibition, increased irritability and hostility and negative affective states which, in turn, are related to aggression and violence (Ireland and Culpin, 2006). Several recent large epidemiological studies have found a link between adolescent delinquency and sleep problems (Catrett and Gaultney, 2009), insufficient sleep amount (Clinkinbeard et al, 2011;Hildenbrand et al, 2013;Meldrum et al, 2015;Peach and Gaultney, 2013) or both (Meijer et al, 2010). However, unanswered questions remain.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Unlike prior years, however, there appears to be much less variation in the range of topics that emerged. The vast majority focused on problem behavior, such as conduct problems (Buil et al 2015), intimate partner violence (Johnson et al 2015 ), delinquency (Meldrum et al 2015), feelings of safety (Côté-Lussier et al 2015), behavioral problems (Vaughan et al 2015), impulse control (Shulman 2015) as well as drug and alcohol use (Abar et al 2015;Fish and Pasley 2015;Ehrenreich et al 2015;TannerSmith et al 2015). In fact, only two articles did not fall in that general focus: one article examined biological stress (Cook et al 2015) and another character development (Wang et al 2015).…”
mentioning
confidence: 99%